Fire behavior of composite beams with simple connections: Benchmarking of numerical models - Fischer, Erica C.; Varma, Amit H. (Journal of constructional steel research, 2015)
This paper focuses on the development and benchmarking of 3D finite element models for predicting the behavior and failure of composite beams with simple (shear) connections subjected to gravity loads and fire conditions, which include both heating and cooling phases. The simple connections included are the shear-tab, single-angle, and double-angle connections commonly used in the U.S. engineering practice. All the structural components including the steel beam, concrete slab, shear connectors, and connection elements (bolts, plates, angles etc.) were modeled in detail using appropriate finite elements, contact interaction models, and material and component behavior at elevated temperature. The detailed finite element models were benchmarked using results from large-scale tests of composite beams and connections subjected to fire loading including heating and cooling phases. The numerical results including the midspan displacement histories and the connection rotation histories were compared with those measured experimentally by the authors. These comparisons indicate that the detailed models reasonably predict the experimental deformation histories and observed failure modes. The models were used to provide additional insight into the axial forces developed in the connections, particularly during the cooling phase, thus enhancing experimental findings. The benchmarked model is recommended for conducting analytical parametric studies to supplement experimental investigations of composite beams and simple connections under fire. •Numerical models for composite beams with simple (shear) connections subjected to combined gravity and fire loading.•Benchmarking of numerical models with experimental results.•Models predict the experimentally measured temperature-dependent beam displacements and connection rotations with reasonable accuracy.•Models predict the development and evolution of temperature-dependent axial force in simple connections, which could not be measured.•Shear-tab connections are subjected to tensile axial forces during the cooling phase, which eventually lead to fracture.